Proceedings of GeoShanghai 2018 International Conference: Tunnelling and Underground Construction (Springer Singapore, 2018)
This book is the fifth volume of the proceedings of the 4th GeoShanghai International Conference that was held on May 27 - 30, 2018. This volume, entitled "Tunneling and Underground Construction", covers the recent advances and technologies in tunneling and underground structure engineering. It presents the state-of-the-art planning philosophy, theories, experiments, methodologies and findings in the related areas. The importance of underground space utilization to the development of human society is also addressed. The challenges and future directions of underground engineering are highlighted. The topics include but are not limited to the tunneling and underground construction induced ground deformation, mechanical behaviors of segmental lining systems, tunneling in challenging situations, maintenance tactic and emergency counter-measures. The book may benefit researchers and scientists from the academic fields of tunneling and underground structure engineering as well as practical engineers from the industry.